VARIABILITY IN GERMAN LEGAL TERMINOLOGY IN LEGAL DOCUMENTS FROM LIECHTENSTEIN - KAKZANOVA, Evgeniya (Comparative Legilinguistics, 2016)
The article deals with the legal language variability in the contract of delegation drawn up in German in Liechtenstein. Time and again the author of the article came across discrepancies in terminology in German-language documents of Germany and other German-speaking countries. As the law in Germany and Liechtenstein developed relatively separately, the changes happening therein resulted in variability of both separate terms, and term systems. The legal system of Germany has been created under the influence of the Roman law among the German tribes and has been developing up till now. The legal system of Liechtenstein was formed under the influence of the Austrian and Swiss law. While the distinctions between Liechtenstein and Germany language standards are minor, the significant divergences from standard forms in the abovementioned countries can be treated as variants.